Effect of Martial Arts Training on Self-Esteem and Discipline in Youth in South Korea - Seoyeon, Shin (International Journal of Physical Education, Recreation and Sports, 2024)
Purpose: The aim of the study was to analyze the effect of martial arts training on self-esteem and discipline in youth in South Korea. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on martial arts training in South Korea shows positive impacts on youth self-esteem and discipline. Through rigorous training, youth gain confidence and a sense of accomplishment. Additionally, martial arts emphasize discipline and respect, fostering focus and adherence to rules. Overall, martial arts serve as a holistic approach to youth development, promoting physical, psychological, and emotional well-being. Unique Contribution to Theory, Practice and Policy: Self-determination theory (SDT), bandura's social learning theory (SLT) & cultural psychology may be used to anchor future studies on martial arts training on self-esteem and discipline in youth in South Korea. Martial arts organizations and instructors should prioritize creating supportive and inclusive training environments that foster positive youth development. Integration of martial arts programs into school curricula and youth development initiatives should be supported through policy initiatives at the national and local levels.